Simple precipitation method to reduce the particle size of glutinous rice flour: physicochemical evaluation - Veni Takarini; Lia A T W Asri; Nina Djustiana; Bambang Kismono Hadi (Materials Research Express, 2022)
Submicron- and nano-sized starch can be employed as organic filler particles in composites. Starch with this size range can be used as an alternative filler for dental impression materials that are used to create an accurate replica or mold of the hard and soft oral tissues. In this work we selected glutinous rice flour as a starch source comprising a high amylopectin content. We carried out two different precipitation methods to reduce the particle size of glutinous rice flour and evaluated the changes on the particle size, morphological, crystallinity, and thermal properties. First precipitation method involved addition of ethanol into an aqueous phase consisting of flour and water, while in the second method (instant precipitation) we added the aqueous phase into the ethanol organic phase. We observed that both methods lead to the decrease of the glutinous rice flour crystallinity from 21.85% to around 4.30%–10.99%. The precipitation also decreased the gelatinization temperature of the treated filler particles from 87.7℃ to around 80.3–85.3℃. We found the morphological transition of glutinous rice flour from polyhedral to nearly spherical-shaped particles. First method resulted in agglomerated particles that were not perfectly distributed. While by employing the instant precipitation method we successfully reduced the particle size from 3411.5 nm to 259.5 nm. To conclude, instant precipitation method offers a simple route to reduce the particle size of glutinous rice flour to submicron-sized range.